A Novel Ultrasonic Technique for the Inspection of a Plate Heat Exchanger - DUBEY, POOJA; F. Declercq, Nico (Canadian Acoustics, 2024)
Biofilm formation in process industries, water treatment devices, and drinking water pipe networks pose a significant risk to public health and cause a variety of operational issues. One of the major challenges is the inspection of biofilms in heat-exchanging devices such as plate heat exchangers. A plate heat exchanger (PHE) is integral to food industries, water treatment plants, and others. Conventional techniques for cleaning biofilm formation in these plates (foulant) include chemical cleaning, steam, and hydro- blasting. However, they are inefficient and labor-intensive because of limitations such as increased handling risk, over-cleaning, and corrosion. Thus, developing novel techniques for real-time monitoring of biofilm growth on these devices is critical for efficient working. Previous studies were restricted to the development of ultrasound-assisted heat exchangers to reduce the deposits in these plates. However, only a few studies have investigated ultrasound as a probable monitoring tool. Thus, this research aims to explore the nonlinear ultrasonic parameters using the second harmonic generation technique as a real-time tool for monitoring biofilms in PHE. The proposed research will help design more effective ultrasonic-assisted plate heat exchangers to achieve maximum heat transfer efficiency.